“I Got Confused Reading It”: Using Backchannels to Collaboratively Build Meaning with Texts - Robyn Seglem; Linda Haling (Journal of Teaching and Learning with Technology, 2018)
This study explores the use of backchannels, real-time online conversations taking place simultaneously with spoken discussions (the front channel), as one approach to meaning-making through discussion. Using transcripts of front and backchannel discussions, we examine how undergraduate preservice teachers utilize backchannels to talk about class-assigned texts. Although previous research has suggested that backchannels can create distractions, our study found that participants within the backchannel groups were able to create meaning through their interactions. We used five types of talk (analytic, personal, intertextual, transparent, and performative) to aid in our analysis. While we found evidence of all types of talk in the transcripts, analytical talk dominated the conversations, suggesting that backchannels can indeed encourage close readings of texts. In addition, we found that the nature of the online environment created a sixth category of talk. This type of talk, which we called negotiation, allowed participants in the backchannel to define and react to the digital space they interacted within. Findings point to increased engagement in class discussion and the potential of backchannels as a way to effectively integrate technology into instruction.